Rethinking literature, knowledge and justice: selecting 'difficult' stories for study in school english - McLean Davies, Larissa; Buzacott, Lucy (Pedagogy, culture & society, 2022)
English remains the only subject mandated throughout the years of schooling in Australia. The compulsory nature of this subject reflects its responsibility for the personal, and literate, development of students. Literature has often been charged with the social and moral dimensions of English. Increasingly, in Australia and elsewhere, literature that disrupts colonial, patriarchal and heteronormative canonical narratives, that presents what might be understood as 'difficult' knowledge, is being selected for study. Drawing on two case stories from current research, this paper explores how text selection and pedagogical practices mediate diverse students' engagements with difficult knowledge in subject English. It explores the challenges teachers face when attempting to disrupt dominant textual meaning-making practices and the decisions they make regarding the kinds of knowledge students encounter in English. We suggest an alternative paradigm- relational literacy- to assist English teachers to reconceptualise students' textual experiences and knowledges in secondary school English.